2018
DOI: 10.1186/s12906-018-2184-y
|View full text |Cite
|
Sign up to set email alerts
|

South African medicinal plant extracts active against influenza A virus

Abstract: BackgroundInfluenza infection remains a major health threat for animals and humans which crucially requires effective antiviral remedies. The usage of herbal medications as readily available alternatives for their compatibility with the body and fewer side effects compared to synthetic chemical treatments has become popular globally. The aim of this study was to investigate and screen in vitro anti-influenza activity of extracts of five South African medicinal plants, namely Tabernaemontana ventricosa, Cussoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 53 publications
1
51
0
Order By: Relevance
“…Medicinal plants have progressively been explored as suitable alternative sources of antiviral agents [20]. Thai medicinal plants have widely been used as a source of herbal medicines because of their high bioactive compound contents that are effective against various diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plants have progressively been explored as suitable alternative sources of antiviral agents [20]. Thai medicinal plants have widely been used as a source of herbal medicines because of their high bioactive compound contents that are effective against various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…extract had the highest total phenol content (220.52 ± 4.47 mM GAE/g sample). The total phenol content of a plant is considered to be an indicator of its antioxidant capacity because the redox properties of the phenolic compounds allow them to act as reducing agents, hydrogen donors, and radical scavengers [20]. Previously, Lee et al [21] reported that ethanolic C. sappan Linn.…”
Section: Discussionmentioning
confidence: 99%
“…The use of alternative medicines is expanding exponentially and is estimated to be generating an annual worldwide market nearing US$60 billion 16. Herbal medicines are used worldwide to treat a variety of medical conditions and mostly cause no ill-effect 1 16–18. Case reports, however, have highlighted-herbal remedies causing toxicity and poisoning due to contamination with other plant materials, heavy metals and microorganisms 2 3.…”
Section: Discussionmentioning
confidence: 99%
“…The quercetin-3-O-α-L-rhamnopyranoside was isolated from Rapanea melanophloeos [55]. The antiviral activity of Q3R against influenza infection was evaluated in our earlier study [54].…”
Section: Immunomodulatory Evaluationmentioning
confidence: 99%